2014
DOI: 10.1186/bf03352537
|View full text |Cite
|
Sign up to set email alerts
|

Modeling investigation of ionospheric storm effects over Millstone Hill during August 4–5, 1992

Abstract: We examine the physical mechanism of the negative and positive storm at middle latitude in August 1992, based on incoherent scatter radar (ISR) observations over Millstone Hill (42.6 • N, 288.5• E) and a first-principles ionospheric model. The exospheric temperature T ex , thermospheric composition and neutral winds, inferred from the ion temperature T i profile using the ion energy balance calculation (e.g., Bauer et al., 1970;Oliver, 1979) and from the electron density N e profile using an ISR data assimil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Zhang et al [20,21] investigated the local time variations of ionospheric drivers such as EUV radiations, neutral compositions, neutral winds, and neutral temperatures, and the correlation of these drivers by assimilating the Incoherent Scatter Radar observations into a middle latitude theoretical model. Lei et al [22] further estimated the ionospheric drivers during the storm and revealed that storm-time disturbed mechanism by the same method.…”
Section: Introductionmentioning
confidence: 96%
“…Zhang et al [20,21] investigated the local time variations of ionospheric drivers such as EUV radiations, neutral compositions, neutral winds, and neutral temperatures, and the correlation of these drivers by assimilating the Incoherent Scatter Radar observations into a middle latitude theoretical model. Lei et al [22] further estimated the ionospheric drivers during the storm and revealed that storm-time disturbed mechanism by the same method.…”
Section: Introductionmentioning
confidence: 96%
“…Mixing of the upper atmosphere accelerates the reduction of the ionosphere due to the atmospheric composition changes (Matsushita, 1959) by upwelling of the molecular-rich air, because atomic oxygen (O) contributes the production and molecular nitrogen (N 2 ) contributes the reduction of the ionosphere (Torr and Torr, 1979). On the other hand, an important mechanism of positive ionospheric storms at mid latitudes is an uplift of the ionosphere due to the upward E × B drift by penetration of magnetospheric electric fields (Martyn, 1953) or due to an equatorward thermospheric wind (Jones and Rishbeth, 1971;Lei et al, 2004). The vertical drift due to electric fields or neutral air winds displaces the equilibrium position of the peak to a new level, at which the upward forcing balances with the downward diffusion along the magnetic field line (Rishbeth, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…These ionospheric data assimilation models include the University of Southern California/the Jet Propulsion Laboratory Global Assimilative Ionospheric Model (USC/JPL GAIM) [ Hajj et al , 2000, 2004; Mandrake et al , 2005; Pi et al , 2003, 2004a, 2004b; Wang et al , 2004], the Utah State University Global Assimilation of Ionospheric Measurements (USU GAIM) [ Scherliess et al , 2004, 2006a, 2006b; Schunk et al , 2003, 2004, 2005; Thompson et al , 2006], and the IonoNumerics model [ Khattatov et al , 2004, 2005]. At the same time, the observations including electron densities, plasma drifts, magnetometer measurements, and so on are also assimilated into models to accomplish some scientific researches [ Eccles , 2004; Lei et al , 2004b, 2004c; Retterer et al , 2005; Richmond and Kamide , 1988; Richmond et al , 1988; Sojka et al , 2001, 2003; Zhang et al , 1999, 2001, 2002, 2003]. In the ionospheric data assimilation applications, a majority of the employed data assimilation methods are 3DVAR [ Bust et al , 2004], 4DVAR [ Pi et al , 2003, 2004a, 2004b], and Kalman filter or its approximations [ Fuller‐Rowell et al , 2004; Hajj et al , 2004; Scherliess et al , 2004].…”
Section: Introductionmentioning
confidence: 99%